Reductive Cyclization of 1,6- and 1,7-Enynes Catalyzed by Iron Complexes - Xi, Tuo; Chen, Xu; Zhang, Heyi; Lu, Zhan (Synthesis, 2016)
Iron-catalyzed reductive cyclization of 1,6- and 1,7-enynes was demonstrated by using an oxazoline iminopyridine ligand. Alcohol, ketone, ester, ether, halide, amine, amide, imine, nitrile, silyl, and alkyne groups are tolerated under the mild reaction conditions. A speculative mechanism is proposed on the basis of deuteration studies. A primary enantioselective transformation was also conducted.
Keywords: iron; catalysis; enynes; cyclizations; asymmetric synthesis